Neonatal sepsis due to non-albicans Candida species and their susceptibility to antifungal agents: first report from Bangladesh (IMC Journal of Medical Science, 2021)
Background and objectives: Frequency of neonatal sepsis in Neonatal Intensive Care Units (NICU) has been increasing worldwide over the last decades. The emergence of non-albicans Candida (NAC) species and their resistance to common antifungal agents become an important preventive and therapeutic issue. The present study was undertaken to find out the role of NAC species in neonatal sepsis/candidemia in the NICUs of hospitals of Dhaka city. The susceptibility pattern of NAC species to antifungal agents was also determined.Materials and methods: Suspected cases of neonatal sepsis admitted in NICU of four tertiary care hospitals of Dhaka city, from March to December 2018 were enrolled. In this cross sectional study, blood samples were collected from neonates with suspected sepsis for culture. Identification of Candida species was done by carbohydrate (CHO) assimilation tests using swab auxanographic technique, CHO impregnated yeast nitrogen base plate method (YNB), microtiter plate based miniaturized method and by HiCromeTM Candida Differential Media. Susceptibility of the isolated Candida species to antifungal agents was determined by disk diffusion (DD) and by minimum inhibitory concentration (MIC) methods. MIC was determined by broth microdilution method using RPMI 1640 and trypticase soy broth (TSB).Results: In the present study, NAC species were isolated from 39.7% neonates. C. tropicalis was the predominant species (81.0%) followed by C. parapsilosis (12.1%), C. auris (5.2%) and C. dubliniensis (1.7%). Isolated NAC species were 98.3% sensitive to voriconazole. Sensitivity to fluconazole, ketoconazole, itraconazole, and clotrimazole was 3.5%, 15.5%, 86.2% and 56.9% respectively by DD method. All the isolates (100%) were sensitive to miconazole and nystatin. All the C. tropicalis, C. auris and C. dubliniensis were sensitive to amphotericin B and anidulafungin. One and four C. parapsilosis were found resistant to amphotericin B and anidulafungin respectively. The MIC results obtained by using RPMI 1640 and TSB as growth medium were concordant suggesting that TSB media was a good alternative to expensive RPMI 1640.Conclusion: The advent of NAC species merits attention as they are highly resistant to most of the azoles. Therefore, speciation of Candida in neonatal candidemia is essential to institute appropriate antifungal therapy.Ibrahim Med. Coll. J. 2020; 14(2): 19-26